The effect of different non-dairy creamer on ready-to-drink milk coffee. Issue 3 (June 2021) - Fibrianto, K; Maharani, Y
Abstract: Milk coffee is greatly favourable instant-coffee among societies as the demand for it is considerably high as it mostly serves blended flavours. RTD (ready-to-drink) milk coffee is one of coffee drink that provide practical value to consumers. Creamer is one of important ingredient used in RTD-milk coffee. Every creamer has different properties which affect the final taste and mouthfeel of the products. This current study was aimed to investigate the effect of non-dairy creamer on sensory profile of RTD-milk coffee. The sensory profile was studied by the JAR (Just-About-Right) method involving 40 respondents. Protein, fat, and total soluble solids as well as viscosity and colour analysis were also assessed. Based on Principal Component Analysis on physical and chemical properties as well as sensory profile, it can be concluded that all non-dairy creamer tested in this study are not sufficiently able to replace the dairy creamer due to their higher fat content (p-value <0.05). Nonetheless, the FM878 is selected among non-dairy creamer as added ingredient for RTD-milk coffee based on JAR analysis.